Factors Affecting Firm Performance of Vietnamese Export-Import Enterprises: A PLS-SEM Approach - DAO, Dat Quoc; TRAN, Phat Quang; NGUYEN, Cuong Quoc; CAO, Minh Hong (Theoretical and Practical Research in Economic Fields; Vol 16 No 1 (2025): TPREF Volume XVI, Issue 1(33), Spring 2025, 2025)
Firm performance improvement is a top priority for export-import businesses. In order to assess corporate social responsibility, this study uses partial least squares structural equation modelling (PLS-SEM) to examine how logistics capabilities and business value mediate the firm performance of import-export businesses in Vietnam. Data is collected through convenient sampling. Samples include 427 respondents who are currently working in Vietnamese import-export companies. The questionnaire survey is distributed to respondents via the Google Form link. SmartPLS software 4.0 is used to process the data. The findings indicated that 05 factors, which are social responsibility, supply chain management, logistical capabilities, and commercial value, impact the companies' performance. Besides, the Brand image also serves as a mediating variable. This study empirically examined the results of earlier research and evaluated the relationship between variables in the research model. Practical Implications for the management of export-import companies are suggested. Additionally, the research limitations and future directions are proposed.